THE CENTRALITY OF THE LIVING FRAMEWORK AND ITS IMPLICATIONS FOR THE QUALITY OF URBAN LIFE: THE CASE OF THE OLD CITY OF CONSTANTINE - Senani Karima; Bousmaha Ahmed (International Journal of Innovative Technologies in Social Science, 2025)
Living in cities imposes a rapid lifestyle subject to the laws and requirements of living in them, as the latter provide the needs of their inhabitants in varying proportions, and city centres are considered the most important living areas. Through this article, we will try to know the relationship between the quality of urban life and the centralized living areas through a field investigation where 50 questionnaires were distributed to the inhabitants of Souika with the help of two elementary schools. After transcribing and analysing the results, it was found that despite the weight of the historical past in every detail of its corners and the services it provides through it or through its surroundings, and despite the deteriorating state of its built framework, which has negatively affected the inhabitants in many aspects of their daily lives, it is still for them the preferred living framework that fulfils their needs and makes them comfortable and satisfied them and shows their attachment to it and their sense of belonging. This is what makes the overall centrality of the old city, including the historical one, not opposed to achieving the quality of urban life in this particular living framework.